2007
DOI: 10.1253/circj.71.911
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Nonstenotic Coronary Atherosclerosis Assessment by Multi-Detector Computed Tomography

Abstract: he ability to evaluate coronary atherosclerotic stenosis using multi-detector computed tomography (MDCT) has been well recognized in the last several years. [1][2][3][4] MDCT has been shown to permit the visualization of the coronary artery lumen and the detection of the plaque morphology with good correlation to intravascular ultrasound (IVUS) after intravenous injection of a contrast agent. 5 In contrast, a number of investigators have demonstrated that plaque burden and the progression of coronary plaque ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…While Achenbach and Leber et al found a comparable degree of correlation with IVUS, both studies report significant biases for overall plaque volume [14,15]. Considerable inter-modality discrepancy has, likewise, been established in a variety of studies quantifying plaque in terms of cross-sectional area [17,18,27].…”
Section: Discussionmentioning
confidence: 99%
“…While Achenbach and Leber et al found a comparable degree of correlation with IVUS, both studies report significant biases for overall plaque volume [14,15]. Considerable inter-modality discrepancy has, likewise, been established in a variety of studies quantifying plaque in terms of cross-sectional area [17,18,27].…”
Section: Discussionmentioning
confidence: 99%
“…24 Additionally, recently published studies underline the feasibility of coronary CTA to even detect coronary plaque and therefore clinically silent CAD. [25][26][27] A certain prognostic impact on the detection of coronary calcification and non-obstructive CAD is therefore assumed. [28][29][30] However, in clinical practice 2 major limitations are apparent: Firstly, coronary calcifications lead to overestimation of coronary stenoses because of blurring artefacts and total obstruction of the coronary lumen, and may significantly impair diagnostic accuracy 31,32 and thus lead to unnecessary invasive angiography.…”
Section: Discussionmentioning
confidence: 99%
“…13 MDCT provides noteworthy information about coronary arteries including not only the presence and degree of stenotic lesions but also of subclinical atherosclerotic plaques. [14][15][16][17][18][19] MDCT can identify atherosclerotic plaques, in vessels with only minimal angiographic disease, with high sensitivity and moderate specificity as compared with intravascular ultrasound (IVUS). Moreover, MDCT can detect significant atherosclerotic plaques in vessels with signs of positive remodeling, which tend to be underestimated by conventional coronary angiography (CAG).…”
mentioning
confidence: 99%